Influence of some sugars on xylanase production by Aspergillus awamori in solid state fermentation - Lemos,Judith Liliana Solórzano (2002)
Aspergillus awamori showed high extracellular endoxylanase (100 U/ml) and beta-xylosidase activities (3.5 U/ml) when grown on milled sugar cane bagasse as the principal carbon source without treatment. Partial characterization of xylanases showed that the apparent values of Km were 3.12 ± 0.05 mg/ml for endoxylanase (in birchwood xylan) and 0.45 ± 0.05 mM for beta-xylosidase (in p -nitrophenyl beta-D-xylanopiranoside). Corresponding values of Vmax were 6.63 ± 0.02 and 0.078 ± 0.02 mumol/min. Gradual repression of endoxylanase activity was observed when increasing concentrations of glucose and xylose (1, 2, 4, 6 and 8 g of carbohydrate / 4 g of sugar cane bagasse) were added to production media. In contrast, beta-xylosidase activity was stimulated using low levels of carbohydrates (1 g xylose or glucose/ 4 g of sugar cane bagasse).